ESCOLA FAMÍLIA AGRÍCOLA DE ORIZONA (GO): Uma Proposta de Educação Camponesa? - (:unkn) unknown (Universidade Federal de Goiás, 2011)
This research's main objective is to understand the EFAORI (in english: Orizona's Family Farm School), an alternative experience focused on educating the peasant young. It is expected to understand how does the school organizes it's policy and itself, and if it has achieved it's goals. Along the history, Brazilian's formal education was organized to guarantee the dominant classes's interests and with the countryside's education it is not different. There is a lack of efficient public policy that provides a preparating education to the peasant young to the life and work on their reality. The EFA's(FFS) started in the 1930s in France and first came to Brazil in 1960, in Espírito Santo, allied with the social fight for land and education. Soon the experience spreads along all Brazilian's regions, to make opposition against the rural education offered to the peasant young. In the end of the 1990s was created the EFAORI, located 130 km away from the capital of Goiás State, Goiânia, in the small town of Orizona(GO). A strong feature of Orizona is the great presence of agricultural activities, so there was a necessity of having a differentiated education to these young, for them to be adapted to their reality. The FFS's main goal is to provide the young good conditions to stay in the farm with quality of life. The FFS are associated with the pedagogy of alternation, in which the students stay a period boarding school, and another period, with the same duration, in the farm, practicing what was learnt in the school. The objective of the school - social environment integration is the complete educative formation of the young, considering their daily realities. The interest for studying this subject came from the disquietude upon the neglected Brazilian's education, particularly in the farms. The FFS shows themselves, not only as an alternative to the dominant model of education, but, mainly, as an education that does not undergo to the dictates of economy, and worries about a social transformation. To get to the results, there was made a questionnaire with 56% of the school's students and interviews with 20% of the egresses from the school in the years of 2007, 2008 and 2009. Informal conversations were also made with students, teachers and other school employees. The EFAORI, as concluded in this research, has contributed to the social emancipation for the young peasant. It was concluded that 70% of the young interviewed migrated to the urban areas to give continuity to their academic life, however, they assumed that they wish to go back to the farms with a better formation, which would improve their family's income. This research is expected to contribute with the experience of FFS, especially the EFAORI, towards allowing some questions about school to be rethought, and it is expected, as well, that the positive points get reinforced, aiming to strengthen this experience which is a good alternative to the farm families.
Family Farm School of Orizona (GO): a proposal for education persant?
Keywords: EFAORI; famílias camponesas; educação; movimentos sociais; EFAORI; farm families; education; social movement; CNPQ::CIENCIAS HUMANAS::GEOGRAFIA::GEOGRAFIA HUMANA::GEOGRAFIA DA POPULACAO